Issues in the Enforcement of Assets and Liabilities Declaration Laws by the National Anti-Corruption Commission (NACC): A Case Study of Temple Abbots - Pongprecha, Nurassakorn; Thianprathuangchai, Mongkol (ARU Research Journal Humanities and Social Sciences, 2026)
This research aimed to examine the concepts, theories, and laws related to the submission of asset and liability accounts of monks in the position of temple abbot. It analyzed the law enforcement problems of the National Anti-Corruption Commission (NACC), compared them with foreign legal frameworks, and proposed appropriate guidelines for developing asset inspection mechanisms for temple abbots to align with the principles of transparency and good governance. The findings indicated that an abbot occupies a dual status as both an official performing legally prescribed administrative functions and a Buddhist monastic subject to the Dhamma and Vinaya. This dual status has resulted in practical inconsistencies in the enforcement of asset and liability declaration requirements. Furthermore, a legislative gap currently exists because the Organic Act on Anti-Corruption, B.E. 2561 (Sections 102 and 103), has not explicitly designated the position of abbot as a mandatory declarant. This absence of clear legal authority has constituted an "opportunity" according to Corruption Theory, potentially leading to conflicts of interest and money laundering within religious organizations. A comparative analysis of five countries (Sri Lanka, Japan, Bhutan, South Korea, and China) demonstrated that most have shifted from individual audits to nstitutional Transparency. Consequently, this study proposes an amendment to Section 102 to clearly define the abbot’s status, establishing a financial threshold and shifting from individual reporting to organizational financial reporting via an E-Temple Financial Registry. Such a paradigm shift would redefine the NACC’s role from a mere regulator to a Compliance Facilitator, ensuring sustainable integrity in religious administration.